The WUS homeobox-containing (WOX) protein family - van der Graaff, Eric (BioMed Central, 2009)
The WOX genes form a plant-specific subclade of the eukaryotic homeobox transcription factor superfamily, which is characterized by the presence of a conserved DNA-binding homeodomain. The analysis of WOX gene expression and function shows that WOX family members fulfill specialized functions in key developmental processes in plants, such as embryonic patterning, stem-cell maintenance and organ formation. These functions can be related to either promotion of cell division activity and/or prevention of premature cell differentiation. The phylogenetic tree of the plant WOX proteins can be divided into three clades, termed the WUS, intermediate and ancient clade. WOX proteins of the WUS clade appear to some extent able to functionally complement other members. The specific function of individual WOX-family proteins is most probably determined by their spatiotemporal expression pattern and probably also by their interaction with other proteins, which may repress their transcriptional activity. The prototypic WOX-family member WUS has recently been shown to act as a bifunctional transcription factor, functioning as repressor in stem-cell regulation and as activator in floral patterning. Past research has mainly focused on part of the WOX protein family in some model flowering plants, such as Arabidopsis thaliana (thale cress) or Oryza sativa (rice). Future research, including so-far neglected clades and non-flowering plants, is expected to reveal how these master switches of plant differentiation and embryonic patterning evolved and how they fulfill their function.